Humanistic Education Practices at SMA Muhammadiyah 2 Mojosari: Praktik Pendidikan Humanistik di SMA Muhammadiyah 2 Mojosari - Rindaningsih, Ida; Azwarnaufal, David Yusuf (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Humanistic education aims to foster students’ holistic growth by integrating cognitive, emotional, and social aspects. Specific Background: SMA Muhammadiyah 2 Mojosari seeks to apply humanistic principles in daily learning to strengthen students’ character and critical thinking. Knowledge Gap: Limited studies address structured implementation of humanistic education in Indonesian Islamic senior high schools. Aim: This study explores strategies, challenges, and outcomes of humanistic education implementation. Results: Findings indicate that student-centered approaches, problem-based learning, and reflective activities encourage autonomy and collaboration. Challenges include limited resources and teacher readiness. Novelty: This research highlights the practical application of humanistic learning within an Islamic school context. Implications: Results provide insight for educators and policymakers to design learning models that balance academic achievement and character formation in similar educational settings. Highlights:• Student-centered humanistic education• Character and critical thinking development• Challenges and practical recommendations Keyword: Humanistic Education, Student Autonomy, Character Formation, Islamic School, Qualitative Study